Evaluation of ISO 4049: water sorption and water solubility of resin cements. (21st February 2017) - Müller, Johannes A.; Rohr, Nadja; Fischer, Jens
Abstract : The aim of this study was to evaluate the water sorption and solubility test design of ISO 4049 for resin cements. Sorption and solubility of six dual‐curing resin cements [RelyX Unicem 2 Automix (RUN), Multilink Speed CEM (MLS), Panavia SA Plus (PSA), RelyX Ultimate (RUL), Multilink Automix (MLA), and Panavia V5 (PV5)] were analyzed by storage in distilled water after dual‐curing. In addition, sorption and solubility during thermal cycling were assessed with self‐cured and dual‐cured specimens. After water storage, all cements revealed sorption in the range of 30  μ g mm −3 except for PV5, for which sorption was markedly lower (mean ± SD = 20.8 ± 0.4  μ g mm −3 ). Solubility values were negative for RUN and RUL (−2.1 ± 0.08  μ g mm −3 and −1.9 ± 0.13  μ g mm −3, respectively). All other cements attained positive values in the range of 0.4–0.8  μ g mm −3 . Thermal cycling effects were more pronounced. The assessment of water sorption according to ISO 4049 provides reliable results. Solubility results must be interpreted with care because absorbed water may distort the values.